2014
DOI: 10.4172/2329-6542.1000108
|View full text |Cite
|
Sign up to set email alerts
|

The Source of the Interplanetary Magnetic Field (IMF) Measured by Pioneer V

Abstract: Solar atmosphere expansion into interplanetary space was a dominant theoretical models when Pioneer-V was launched in March 1960, to determine among others the source of measured anomalous Interplanetary Magnetic Fields (IMF); lacking alternatives, the experimenters endorsed the solar-wind theory; this paper noticed loopholes in that endorsement; such as the probe's failure to detect any increase in IMF for fifty five minutes, and a maximum horizontal magnetic field was recorded at three Earth Magnetic Observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Since the concept of solar atmosphere extension and expansion into interplanetary space [18] endorsed by Pioneer V [19], showed to contain loopholes [20], and Magnetosphere breached continually by solar wind in several places [21], it is suggested that, both the flow of energetic protons [22], and energetic electrons >200 keV [23], in Magnetosheath, and the concentration of high density solar wind positive ion ranging between 35 to 127 cm -3 at Magnetosheath [22], contrary to background proton's density of 5-10 cm -3 [24], and Magnetosheath plasma interaction with magnetosphere at magnetopause, which results in fluctuations and strong magnetic fields, leading to an intense geomagnetic storm Dst<200 n Tesla [25], a situation which is similar to the ionospheric elongated diamagnetic cavity created after High-altitude Nuclear Detonation (HND) [1], therefore it is suggested that, both MS and HND are similar in nature, and resulted from charged particles interaction with geomagnetic field.…”
Section: High-altitude Nuclear Detonations (Hnd) and Magnetic Storms mentioning
confidence: 99%
“…Since the concept of solar atmosphere extension and expansion into interplanetary space [18] endorsed by Pioneer V [19], showed to contain loopholes [20], and Magnetosphere breached continually by solar wind in several places [21], it is suggested that, both the flow of energetic protons [22], and energetic electrons >200 keV [23], in Magnetosheath, and the concentration of high density solar wind positive ion ranging between 35 to 127 cm -3 at Magnetosheath [22], contrary to background proton's density of 5-10 cm -3 [24], and Magnetosheath plasma interaction with magnetosphere at magnetopause, which results in fluctuations and strong magnetic fields, leading to an intense geomagnetic storm Dst<200 n Tesla [25], a situation which is similar to the ionospheric elongated diamagnetic cavity created after High-altitude Nuclear Detonation (HND) [1], therefore it is suggested that, both MS and HND are similar in nature, and resulted from charged particles interaction with geomagnetic field.…”
Section: High-altitude Nuclear Detonations (Hnd) and Magnetic Storms mentioning
confidence: 99%